(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Today’s technological development increasingly demands the importance of information for every organization, both government and private, because basically the whole part of the organization requires training as a supporting process of administrative work and the implementation of management functions, and planning, determining the realization of organizational goals. The objective cannot be realized without an active role and the accuracy of work or effectiveness of employees, even though the tools owned by the agency are so sophisticated, the sophisticated tools owned by the agency have no benefit to the agency, if the role is not included. Managing employees is difficult and complex, because they have heterogeneous thoughts, feelings, status, and background that are under the organization. The purpose of this study is to find out the Work Effectiveness of employees at the Regional Library and Archives Service Office of the Talaud Islands Regency. The theory used is Work Effectiveness. The research method used is a qualitative research method to find answers to questions related to Employee Work Effectiveness. These questions require answers that are descriptive in nature that describe the facts about the problems being investigated as there are rational interpretations of various findings in the field while analyzing all the conditions in the location of the study. Based on the results of the study, the work effectiveness of employees at the Library and Archives Office of the Talaud Islands Regency, is still experiencing problems such as employees who are still less consistent in managing time, as well as facilities that are still lacking and human resources are still poor, so the work is still not fully effective and efficient. Keywords: Effectiveness, Work, Employees